2004
DOI: 10.1051/apido:2004063
|View full text |Cite
|
Sign up to set email alerts
|

Development of hypopharyngeal glands in adult honey bees fed with a Bt toxin, a biotin-binding protein and a protease inhibitor

Abstract: -To investigate potential impacts of insecticidal transgene products on hypopharyngeal gland development, newly-emerged adult honey bees were kept in cages and fed for ten days with a pollen-food to which one of the following proteins had been added at concentrations equivalent to pollen expressing 1.25% (of total protein) aprotinin, 11.2 µM avidin or 0.3% Cry1Ba protein. Control bees were fed pollenfood without additive, with casein added, or pollen-candy. None of the treatments significantly affected bee sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 38 publications
6
34
0
1
Order By: Relevance
“…Soybean trypsin inhibitor (SBTI) can also have a negative effect on the development of HPGs. Malone et al (2004), Sagili, Pankiw, and Zhu-Salzman (2005), and Babendreier et al (2005) also demonstrated a decrease in HPGs protein content in adult honey bees whose diet contained transgenic products as toxin Bt, biotin-binding protein (avidin), and a protease inhibitor (aprotinin).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Soybean trypsin inhibitor (SBTI) can also have a negative effect on the development of HPGs. Malone et al (2004), Sagili, Pankiw, and Zhu-Salzman (2005), and Babendreier et al (2005) also demonstrated a decrease in HPGs protein content in adult honey bees whose diet contained transgenic products as toxin Bt, biotin-binding protein (avidin), and a protease inhibitor (aprotinin).…”
Section: Discussionmentioning
confidence: 94%
“…Our work is the first study presenting a profile of proteolytic activity along with protein profile. In our study, we used extracts from whole bees, so it is important to remember that proteases and inhibitors occur in many tissues and fulfill different functions in the biology of insects, from food secretion and digestion (Chapman, 1998;Deseyn & Billen, 2005;Li et al, 2008;Liu et al, 2013) to metamorphosis (Lima, BrochettoBraga, & Chaud-Netto, 2000;Malone, Todd, Burgess, & Christeller, 2004;Strachecka, Gryzińska, & Krauze, 2010;Strachecka, Paleolog, & Grzywnowicz, 2008) and immune mechanisms (Evans et al, 2006;Frączek et al, 2013). It is also well known that some enzymes fulfill detoxification functions, because they take part in the metabolism of pesticides (Shi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Proteases play a prominent role in a wide array of physiological processes such as food digestion, blood clotting, embryogenesis, tissue reorganization, defense mechanisms and immune responses (Schoofs and Salzet 2002). Proteolytic enzymes are known to be present in the bee alimentary duct, hemolymph, moult liquid, venom and on the body surface (Terra and Ferreira 1994, Bode et al 1999, Lima et al 2000, Malone et al 2004, Evans et al 2006, Strachecka et al 2011. Up to date, the body-surface proteolytic system of mites has not been analysed.…”
Section: Introductionmentioning
confidence: 99%
“…2 and 3). (Lima et al, 2000;Otlewski et al, 2001;Deraison, 2004;Malone et al, 2004;Evans et al, 2006;Strachecka and Grzywnowicz, 2008;Strachecka et al, 2010;Grzywnowicz et al, 2009;Andrejko and Mizerska-Dudka, 2011;Frączek et al, 2013). Proteinase activity is important for O. rufa that feed on high protein diets composed mainly of pollen (Brodschneider and Crailsheim, 2010).…”
Section: Resultsmentioning
confidence: 99%